PHYTOPLANKTON COLLECTED DURING THE FIBEX CRUISE OF THE UMITAKA MARU III, 1980-1981; A PRELIMINARY REPORT (Collected Abstracts of Transactions of the Tokyo University of Fisheries No. 5,March 1982) - IORIYA, Teru; KATO, Mitsuo (1982)
P(論文) departmental bulletin paper